Cryogenic pulsed laser deposition of ZnO - Bruncko, Jaroslav; Vincze, Andrej; Netrvalová, Marie; Šutta, Pavol; Michalka, Miroslav; Uherek, František (Vacuum, 2012)
The paper deals with the pulsed laser deposition technology and in this special case the substrate was cooled at cryogenic temperature by liquid nitrogen during the deposition process. This approach is proper for growth of highly disordered structures with new physical properties and zinc oxide was applied as experimental example for demonstration. Films were deposited on different substrates: Si (100) and sapphire (0001) and subsequently annealed at different temperatures (200–800 °C). Their properties were investigated by various analytical methods. X-ray diffraction (XRD) proved fully amorphous structure of as-grown ZnO layers which were cooled during the deposition process. Annealing of these amorphous layers changed their properties according to temperature level and annealing time. XRD and scanning electron microscopy (SEM) revealed recrystallized structure. According to the secondary ion mass spectroscopy (SIMS) the layers has homogenous chemical composition along the depth profile with improved homogeneity after annealing. ► PLD provides special opportunity for growth of amorphous thin films. ► Undoped ZnO was applied as the demonstration example. ► As-grown samples exhibited fully amorphous and stable structure. ► Annealing of amorphous films led to the recrystallization process. ► Properties of recrystallized structures varied according to annealing temperature.